2009
DOI: 10.1016/j.humimm.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory profiles in liver transplant recipients on different immunosuppressive agents

Abstract: We compared peripheral blood immunophenotyping in 31 adult liver transplant recipients on differing long-term immunosuppressive (IS) monotherapy with and without peri-transplantation alemtuzumab (AL) induction. All patients had been stable on monotherapy with either sirolimus (SRL) (n = 10) or without SRL (tacrolimus (TAC) (n = 10), mycophenolate mofetil (MMF) (n = 11)) for more than 6 months. Five-color flow cytometry for putative “regulatory” T and dendritic cells as well as serum assays for soluble HLA-G (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
(27 reference statements)
2
23
0
1
Order By: Relevance
“…Moreover, a significant increase in Treg percentages in the peripheral blood of AL-treated renal transplant recipients persisted only if CNI therapy was withdrawn [9]. As have others [20], we have also demonstrated inhibitory effects of TAC on Treg generation in contrast to SRL, both in vitro and in vivo [12,15]. The long-term persistence of these effects in AL treated patients, however, still needs to be evaluated.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, a significant increase in Treg percentages in the peripheral blood of AL-treated renal transplant recipients persisted only if CNI therapy was withdrawn [9]. As have others [20], we have also demonstrated inhibitory effects of TAC on Treg generation in contrast to SRL, both in vitro and in vivo [12,15]. The long-term persistence of these effects in AL treated patients, however, still needs to be evaluated.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, although we and others have reported clinical and ex vivo data on maintenance IS agents favoring higher Treg generation with SRL versus calcineurin inhibitors [11,12], it was questioned what the additional influence of AL would be with these maintenance agents i n vitro on this Treg subset. Consequently, we now report on (1) a proposed mechanism of the regulatory effects in MLR unique to AL, and (2) the contrasting effects in MLR of AL in combination with TAC versus SRL.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data in transplantation reported that although many immunosuppressive drugs (MMF, cyclosporine, and sirolimus) were found to have no effect on serum HLA-G level (34,35), other antiproliferative drugs such as everolimus (34) and tacrolimus (35) may be associated with the increase in serum HLA-G and better graft outcome. In our study, we did not detect correlation between immunosuppression drugs and serum HLA-G levels; thus, we believe that the findings of increased HLA-G levels in the drug-free tolerant patients relates largely to the clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation is the lack of an objective biomarker of immune function to distinguish the so-called immunosuppressed subjects from controls. However, immunosuppression is difficult to quantify in this setting using a single assay, owing to the differing effects of each immunosuppressive drug on T-cell subsets and cytokine expression [42,43].…”
Section: Discussionmentioning
confidence: 99%